(untitled) (Materiali di Estetica. Terza serie, 2017)
For Philo the unique true artist is God who makes the Great City, the world. He designs a plan and, being the author of the eternal paradigms, he produces many perfect shows: the dance of the stars, the heavenly music, the echo of non-visible sounds. In the human world, art to be true art and not a form of falsehood, must follow noetic patterns. We can see this aspect in the visual arts, where an artist acts -Bezalel- who draws inspiration from divine indications. Phidias too, even if he is not inspired, brings the ideal types in the matter. There is an ontological descent from the divine work to the products imitating ideal paradigms, to the artifacts gifted with an empirical agreeableness, even if they do not ascend to the idea. In the literary field too, the texts of authors such as Solon or Plato show elements of truth: they are third level works, but they are not negative. The status of the theatre is quite different: the performances seem necessarily to involve forms of falsehood, simulation, deceit. My hypothesis is that the theatre has a particular role: it is its own nature to be false, not simply illusion, but real deception. It is not a question of being an inferior copy of an ideal eternal model, but of being actually falsehood and lie. Thus, for Philo theater is at a much inferior level than the other arts and in this, Philo is quite different from Plato.